The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/02757250009532417
|View full text |Cite
|
Sign up to set email alerts
|

On the potential of CHRIS/PROBA for estimating vegetation canopy properties from space

Abstract: The Compact High Resolution Imaging Spectrometer (CHRIS), to be launched on board the PROBA (Project for On-Board Autonomy) satellite in 2001/2002, will provide remotely-sensed data for terrestrial and atmospheric applications. The mission is intended to demonstrate the potential of a compact, low-cost, imaging spectrometer when combined with a small, agile satellite platform. CHRIS will provide data in 18-62 user-selectable spectral channels in the range 400 nm to 1050 nm (1.25 nm -11 nm intervals) at a nomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Although these are not very realistic scenarios, they allow us to examine the effect of multiangular sensing in the most extreme case of backward and forward scattering. The range of spectral wavebands used here correspond to those employed by a range of current satellite-sensors (Table 2; AVHRR, MODIS, MISR, MERIS, VEGETATION and CHRIS), which have proved to be useful in the retrieval of surface biophysical properties (Abuelgasim et al, 2006;Barnsley et al, 2000;Knyazikhin et al, 1998b).…”
Section: Lut Sampling Schemementioning
confidence: 99%
“…Although these are not very realistic scenarios, they allow us to examine the effect of multiangular sensing in the most extreme case of backward and forward scattering. The range of spectral wavebands used here correspond to those employed by a range of current satellite-sensors (Table 2; AVHRR, MODIS, MISR, MERIS, VEGETATION and CHRIS), which have proved to be useful in the retrieval of surface biophysical properties (Abuelgasim et al, 2006;Barnsley et al, 2000;Knyazikhin et al, 1998b).…”
Section: Lut Sampling Schemementioning
confidence: 99%
“…The parameter combination that yields the closest spectrum in the database is considered to be the inversion solution [26]. The major advantage of the LUT-based approaches is that the forward modeling is divorced from the inversion procedure, and hence can be used for inversion of any complex model like DART [15,27].…”
Section: Introductionmentioning
confidence: 99%
“…Weiss et al [32] reported that only a limited number of wavebands are required for canopy biophysical variable estimation. Other studies have stated that the selection of a subset of spectral bands can lead to a more stable and accurate inversion [27,31]. However, a general criterion for the selection of bands has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%
“…While much work exists in the domain of retrieving the canopy biophysical variables from model inversion methods using a variety of optimization methods (Baret et al, 1995;Barnsley et al, 2000;Bicheron and Leroy, 1999;Combal et al, 2002;Goel et al, 1984;Jacquemoud & Baret, 1993;Knyazikhin et al, 1998a;Kuusk, 1991), applications of support vector machines in remote sensing problems are focused mainly towards classification (Banerjee et al, 2006;Durbha & King, 2005 Wohlberg et al, 2006) and to the best of our knowledge little work has been reported towards the application of support vector regression (SVR) for the retrieval of biophysical variables from inversion of canopy radiative transfer models.…”
Section: Introductionmentioning
confidence: 99%